Anchoring Effects in Facial Attractiveness. (October 2018) - Goller, Juergen; Leder, Helmut; Cursiter, Heather; Jenkins, Rob
First impressions from faces emerge quickly and shape subsequent behaviour. Given that different pictures of the same face evoke different impressions, we asked whether presentation order affects the overall impression of the person. In three experiments, we presented naturally varying photos of a person's face in ascending (low-to-high) or descending (high-to-low) order of attractiveness. We found that attractiveness ratings for a subsequent test item were higher for the descending condition than for the ascending condition (Experiment 1), consistent with anchoring effects. In Experiment 2, we ruled out contrast between the final item and the test item as the cause of the effect by demonstrating anchoring within the sequence itself. In Experiment 3, we found that order of image presentation also affected dating decisions. Our findings demonstrate that first impressions from faces depend not only on visual information but also on the order in which that information is received. We suggest that models of impression formation and learning of individual faces could be improved by considering temporal order of encounters.